Ukrainian diaspora in Los Angeles - Iryna Hetman-Piatkovska (Американська історія і політика, 2017)
This article investigates the formation, development, and activity of the Ukrainian diaspora from 1920 through the beginning of 2016 in the city of Los Angeles. Provides an overview of the historical role that the Ukrainian Cultural center and the Ukrainian Orthodox Church of St. Vladimir, in Los Angeles, played in consolidating Ukrainian communities.